Ceratocystis quercicola sp. nov. from Quercus variabilis in Korea. Issue 4 (3rd July 2020) - Cho, Sung-Eun; Lee, Dong-Hyeon; Wingfield, Michael J.; Marincowitz, Seonju
Abstract: During a survey of putative fungal pathogens infecting oak trees in the Gangwon Province of the Republic of Korea, a fungus resembling a Ceratocystis sp. was repeatedly isolated from natural wounds on Quercus variabilis . Morphological comparisons and DNA sequence comparisons based on partial β-tubulin and TEF-1α gene regions showed that the fungus resided in a distinct lineage. This novel Ceratocystis species is described here as C. quercicola sp. nov. This is the first novel species of Ceratocystis to be reported from Korea. A pathogenicity test showed that it can cause lesions on inoculated trees but that it had a very low level of aggressiveness. The discovery of this fungus suggests that additional taxa residing in Ceratocystis are likely to be discovered in Korea in the future.